Tensile and compressive behaviour of early age concrete - Barraclough, Andrew (Precast/Prestressed Concrete Institute, 2012)
This paper presents a series of experimental tensile results that have been conducted on concrete at early age, typically less than 3 days. The test method and procedure for measuring uniaxial tensile strength using concrete cylinders are reported. The tensile strain capacity of concrete under uniaxial tension using the adopted direct tension test method is presented. The test method adopted seeks to overcome the difficulties of centralizing and aligning the test specimen, and eliminates direct point loading from either steel reinforcement [1] or using square sections [2], which can influence the post ultimate strain softening. This paper presents the relationship between direct and indirect tensile strengths and compressive strength of typical precast concrete panel mix and shows their correlations. The significance of understanding the behaviour of concrete in tension is detailed and the role of tensile properties with fracture mechanisms is explored. It is shown that the relationship between tensile strength is not dependent on compressive strength and more reliant on mix composition and concrete age. It is also demonstrated that indirect and direct tensile tests will reflect different tensile strengths. The conclusion summarises that the tensile strength, less than 3 days old, measured by the test method employed and highlights the differences against tensile split tests, and compression cylinders.